2017
DOI: 10.1186/s12887-017-0929-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stunting and severe stunting among Burundian children aged 6-23 months: evidence from a national cross-sectional household survey, 2014

Abstract: BackgroundBurundi is one of the poorest countries and is among the four countries with the highest prevalence of stunting (58%) among children aged less than 5 years. This situation undermines the economic growth of the country as undernutrition is strongly associated with less schooling and reduced economic productivity. Identifying the determinants of stunting and severe stunting may help policy-makers to direct the limited Burundian resources to the most vulnerable segments of the population, and thus make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
67
3
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 23 publications
(41 reference statements)
28
67
3
14
Order By: Relevance
“…One other risk factor suggested from our analysis was households having more than one young child (less than two years old). Similar findings have been reported in other developing countries (Nkurunziza, Meessen, Van geertruyden, Korachais, 2017;Mbuya, Chidem, Chasekwa, Mishra, 2010). When families have more children competing for resources, the odds of stunting for the children is understandably higher.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One other risk factor suggested from our analysis was households having more than one young child (less than two years old). Similar findings have been reported in other developing countries (Nkurunziza, Meessen, Van geertruyden, Korachais, 2017;Mbuya, Chidem, Chasekwa, Mishra, 2010). When families have more children competing for resources, the odds of stunting for the children is understandably higher.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment of drinking water has a significant impact on the reduction of morbidity related to infectious and diarrheal diseases among children less than 24 months. Diarrhea can cause loss of appetite and hinder nutrient absorption, which in turn can cause growth retardation in infants and children (Nkurunziza, Meessen, Van geertruyden, & Korachais, 2017;Sharma, Arvind Kumar., Baig, Vaseem, Yadev, 2010). Mothers who were educated are more likely to be empowered to make decisions to provide children such basic necessities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rural residence (only in model 2 for moderate stunting) and smaller than average size at birth are more likely to be stunted. These results are also reported in other studies [54,55,48,56]. Mother and Fathers' higher education status is associated significantly with the less likelihood of child of less than five years being stunted (moderate and severe) in Punjab, Pakistan.…”
Section: Discussionsupporting
confidence: 86%
“…Among the non‐nutritional findings in this study, we found an inverse association of increasing number of adults in the household with anaemia in infants/toddlers. In low‐ and middle‐income countries, large family sizes have been identified as a factor associated with malnutrition (Keino, Plasqui, Ettyang, & van den Borne, ; Pelto et al, ), especially when high numbers of children live in the same household (Nkurunziza, Meessen, Van Geertruyden, & Korachais, ). In the infant/toddler group, the odds of anaemia fell 31% for each additional adult living in the same household.…”
Section: Discussionmentioning
confidence: 99%